From Decline to Rebound: Analyzing the Dynamics of Fertility Trends in Sleman Regency Amid Global Shocks, 2018-2022 - Alfana, Muhammad Arif Fahrudin (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2024)
This quantitative study aims to examine the trends of live birth rates in Sleman Regency over a five-year period (2018-2022). The study utilizes birth data obtained from the Ministry of Home Affairs (Kemendagri). The analysis focuses exclusively on live birth data without considering socio-economic indicators or environmental factors. The findings indicate that Sleman Regency experienced significant fluctuations in fertility trends amidst global challenges, including the Covid-19 pandemic. Initially, the fertility environment was stable, with a slight increase in live births from 13,102 in 2018 to 13,354 in 2019. However, a notable decline to 11,702 live births was observed in 2021, followed by a robust rebound to 14,908 live births in 2022. The study highlights the resilience of Sleman Regency’s demographic dynamics in the face of global disruptions. These findings underscore the importance of continuous monitoring and analysis of demographic data to anticipate and manage future demographic shifts. This research contributes to the demographic field by providing insights into the fluctuating fertility patterns in a specific region during a period marked by global disruptions.